2019
DOI: 10.1038/s41598-019-53810-1
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section, but not induction of labour, is associated with major changes in cord blood metabolome

Abstract: The physiology of how prelabour caesarean section (PCS) and induction of labour (IOL) in comparison to spontaneous vaginal delivery (SVD) has not been fully clarified yet. We measured 201 cord blood (CB) phospholipids and energy metabolites via LC/MS-MS in 109 newborns from the ROLO Kids study; metabolites were compared across the three parturition groups via linear mixed models with correction for multiple testing. In comparison to SVD, PCS babies had lower non-esterified fatty acids (NEFA), including sum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We speculate that these unexpected findings are related to a metabolic switch that occurs during the perinatal transition . Labor is a highly coordinated process, associated with changes in maternal and fetal metabolism . Birth itself is associated with profound metabolic and transcriptomic changes in the newborn to maintain energy supply after losing the steady supply of maternal nutrients .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We speculate that these unexpected findings are related to a metabolic switch that occurs during the perinatal transition . Labor is a highly coordinated process, associated with changes in maternal and fetal metabolism . Birth itself is associated with profound metabolic and transcriptomic changes in the newborn to maintain energy supply after losing the steady supply of maternal nutrients .…”
Section: Discussionmentioning
confidence: 92%
“… 30 Labor is a highly coordinated process, associated with changes in maternal and fetal metabolism. 31 , 32 Birth itself is associated with profound metabolic and transcriptomic changes in the newborn to maintain energy supply after losing the steady supply of maternal nutrients. 33 , 34 The placental and cord serum metabolomes were collected at the same postdelivery time point and likely reflect profound metabolic changes in this critical window, whereas maternal serum collected during the third trimester reflects a different developmental window.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in delivery methods were later shown to have profound changes to the infant metabolome. For example, cesarean-delivered babies had substantially lower glucose, inulin, non-esterified fatty acids, and acylcarnitine levels when compared to vaginal-delivered babies ( Marchioro et al, 2019 ). Community differences within the intestinal microbiota is also observed between babies that were breast-fed and formula-fed, where breast-fed babies were found to have a greater abundance of species belonging to Lactobacillus and Bifidobacterium when compared to formula-fed infants ( Phan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that the birth route, either vaginal or c-section, results in dramatic differences in the resident microbiota of the nasopharyngeal, skin, gut, and oral cavities ( Shao et al, 2019 ). Babies that were delivered by c-section were found to have a microbiota that was dominated by Staphylococcus and Streptococcus , whereas vaginal delivery resulted in an increased abundance of Lactobacillus species ( Marchioro et al, 2019 ). The differences in delivery methods were later shown to have profound changes to the infant metabolome.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the metabolic traits related to metabolic syndrome in an adult population may be beneficial during pregnancy and may also be involved in the labour process. Recently, Marchioro et al described how mothers who underwent a planned caesarean section showed lower levels of non-esterified fatty acids (NEFA) and acylcarnitines when compared with mothers who underwent a vaginal delivery with labour [476]. We hypothesised that the SCFA found in the amniotic cavity could be responsible for the observed association between the maternal microbiota at the time of delivery and the immune status of the amniotic fluid cavity.…”
Section: Discussionmentioning
confidence: 93%